ANALYSIS OF GENERATION Z'S SOCIAL MEDIA MARKETING ACTIVITIES RELATIONS ON BRAND EQUITY: CONTEXT ON FASHION PRODUCTS - Vidyanata, Deandra; Irmal, Irmal; Hanika, Ita Musfirowati; Kusuma, Rr. Chusnu Syarifa Diah; Seseli, Eka Merdekawati (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
The fashion industry in Indonesia continues to proliferate, driven by stable economic growth and increasingly dynamic changes in people's consumption patterns. As future consumers, generation Z has unique preferences, behaviors and expectations regarding interactions with fashion brands and products. In this context, it is essential to understand how social media marketing activities, brand experience, and brand trust influence the brand equity of fashion products in Indonesia, especially in the context of Generation Z. The main objective of the research is to analyze the influence of social media marketing activities, brand experience, and brand trust on brand equity. The sample in this study consisted of 160 Generation Z respondents in Indonesia who were determined using a convenience sampling approach. Data collection uses a questionnaire instrument, which is then distributed online. Data analysis uses the SPSS application by displaying data processing results through testing research instruments with validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis, it is stated that social media marketing activities, brand experience, and brand trust have a positive and significant effect on brand equity. In the context of theoretical implications, this research contributes to developing more relevant and comprehensive marketing theories that can better explain Generation Z consumer behavior. Practically, this research will provide valuable guidance for fashion brands in developing more effective and sustainable marketing strategies to reach Generation Z in Indonesia.